ANALISIS PELAKSANAAN PENYUSUTAN BERKAS REKAM MEDIS INAKTIF - Maisharoh Maisharoh; Irvan Irvan (Ensiklopedia of Journal, 2020)
Medical record file storage system is very important to be carried out in a health care institution. The purpose of this study was to analyze the implementation of inactive medical record file depreciation in the Padang Air Dingin Health Center. This type of research is qualitative with a phenomenological approach. Informants in this study were 5 people, all informants were examined using in-depth interview guidelines, to the head of the medical record, registrar and storage officer, using a voice recorder based on interview guidelines that have been made. The results of the study found that there was still a lack of human resources in the depreciation section inactive medical records, the implementation of medical record file depreciation has not been done routinely because there is no workforce for shrinking medical record documents, because the number of filling officers is still limited. There are deficiencies in infrastructure, especially depreciation rooms, and there are no SOPs.